Helping the weak deal with food insecurity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
seminar in Belgium, from 26 to 30 October 1998, in collaboration with the Catholic University of Leuven